THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF SOCIOLOGICAL RESEARCH OF VOLUNTEERING - Olga P. Noskova (Russian Studies in Culture and Society)
The article reveals the theoretical and methodological foundations of the study of volunteering in sociology in the aspects of social activity and social institution. Volunteerism is considered as an interdisciplinary concept, while attention is focused on the fact that sociology and its individual branches occupy a special place in the multidisciplinary study of volunteerism. The development of volunteerism in the context of social history is analyzed and periodization is determined, it is shown that volunteer activity is closely connected with the historical and social development of communities and states, as well as with the formation of civil society. Also, volunteering is analyzed through the prism of a social institution that forms a certain system of life values and attitudes that assume a unifying function, communicative, regulatory, the function of forming and consolidating social relations. It is concluded that the topic of the development of volunteerism is relevant in the global humanitarian sense and volunteerism can be considered as an element of civil society and a tool for strengthening public solidarity.